Faktor Meningkat dan Menurunnya Keimanan: Studi Kitab Tafsir Al-Azhar Karya Buya Hamka - Teguh Saputra (Jurnal Riset Agama, 2022)
This study aims to discuss the factors of increasing and decreasing faith in the book of al-Azhar interpretation. This study uses a qualitative research method with the type of library research (Library research) with the primary source in the form of the book of interpretation of al-Azhar by Buya Hamka and secondary sources in the form of books, theses, articles and other scientific works related to the title of this research and apply content analysis as follows. a tool to analyze the collected data so that it can be described in detail and systematically. The results and discussion of the research are that faith means believing with the heart, making a vow with the tongue and practicing with the limbs then the main cause of increasing faith is obedience to Allah and His Messenger as Buya Hamka's interpretation of Surah al-Imran verse 173 that strong faith is born when the focus of all memory is only on Allah, only hoping for His pleasure, and only fearing Him then the main cause of the decline of faith is being tempted by the devil's whispers as Buya Hamka's interpretation of surah al-Araf verse 16-17 that the devil or devil always tempts humans from four directions, namely front, back, right and left so that humans do bad deeds and the procedure for maintaining faith is to strengthen monotheism, always worship Allah, always carry out good deeds and stay away from bad deeds, seek religious knowledge (Islam), contemplate the signs His greatness and power, and protect the social environment. This study concludes that human faith in Allah, Allah's Angels, Allah's books, Prophets and Apostles, the Day of Judgment, and qada and qadar can increase and decrease but when faith falls, it must be strengthened again. This study recommends conducting in-depth research related to procedures for maintaining faith in Islamic teachings.